2016
DOI: 10.1105/tpc.16.00600
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis TH2 Encodes the Orphan Enzyme Thiamin Monophosphate Phosphatase

Abstract: To synthesize the cofactor thiamin diphosphate (ThDP), plants must first hydrolyze thiamin monophosphate (ThMP) to thiamin, but dedicated enzymes for this hydrolysis step were unknown and widely doubted to exist. The classical thiaminrequiring th2-1 mutation in Arabidopsis thaliana was shown to reduce ThDP levels by half and to increase ThMP levels 5-fold, implying that the THIAMIN REQUIRING2 (TH2) gene product could be a dedicated ThMP phosphatase. Genomic and transcriptomic data indicated that TH2 correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(93 citation statements)
references
References 65 publications
1
90
0
Order By: Relevance
“…Since this is the first plant protein to exhibit this type of enzymatic activity, we will name this enzyme ThMPase1. However, knockouts of ThMPase1 in Arabidopsis have not revealed any visible phenotype or modification of thiamin concentration, even when combined with other mutant lines affected in thiamin monophosphate content Mimura et al, 2016).In this report, we show that PPsPase1 and PECP1 (but not ThMPase1) constitute robust and sensitive reporters of Pi status, indicating a very dynamic expression response to Pi concentration. Using a reverse genetics approach, we altered the expression of these proteins and revealed that PPsPase1 and PECP1 are likely involved in the recycling of polar heads from membrane lipids, but do not play a role in the overall regulation of membrane lipid composition or plant responses to Pi starvation.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Since this is the first plant protein to exhibit this type of enzymatic activity, we will name this enzyme ThMPase1. However, knockouts of ThMPase1 in Arabidopsis have not revealed any visible phenotype or modification of thiamin concentration, even when combined with other mutant lines affected in thiamin monophosphate content Mimura et al, 2016).In this report, we show that PPsPase1 and PECP1 (but not ThMPase1) constitute robust and sensitive reporters of Pi status, indicating a very dynamic expression response to Pi concentration. Using a reverse genetics approach, we altered the expression of these proteins and revealed that PPsPase1 and PECP1 are likely involved in the recycling of polar heads from membrane lipids, but do not play a role in the overall regulation of membrane lipid composition or plant responses to Pi starvation.…”
mentioning
confidence: 77%
“…Since this is the first plant protein to exhibit this type of enzymatic activity, we will name this enzyme ThMPase1. However, knockouts of ThMPase1 in Arabidopsis have not revealed any visible phenotype or modification of thiamin concentration, even when combined with other mutant lines affected in thiamin monophosphate content Mimura et al, 2016).…”
mentioning
confidence: 99%
“…., 2015). By contrast, the pale green 1 (pale1) mutant, impaired in the TMP phosphatase, TH2 (At5g32470), is deficient in leaf TDP (Mimura et al, 2016, Hsieh et al, 2017. We examined the B 1 vitamer profile of these lines and could confirm that TDP was increased in THIC THI1 OE but decreased in pale1 ( Figure 3B).…”
Section: Studies In Rat Brain and E Coli Demonstrate That The Tdp VImentioning
confidence: 97%
“…Conversely, seedling defects have been noted for weak alleles of several EMB genes listed in Table 4 (Conklin et al, 2000;Song et al, 2004;Noutoshi et al, 2005;Mo et al, 2006). Seedling mutant phenotypes have also been documented for Arabidopsis auxotrophs altered in eight additional genes required for the biosynthesis of thiamine (Komeda et al, 1988;Papini-Terzi et al, 2003;Raschke et al, 2007;Mimura et al, 2016), tryptophan (Last & Fink, 1988), riboflavin (Ouyang et al, 2010;Hedtke et al, 2012), and isoleucine (Yu et al, 2013). Seedling defects in the trp1 auxotroph are not rescuable by tryptophan (Last & Fink, 1988) because other intermediates in tryptophan biosynthesis are required for auxin-mediated plant growth and development.…”
Section: Embryo Defectives and The Search For Plant Auxotrophsmentioning
confidence: 99%